Performance analysis for pseudo-random asynchronous FH-CDMA system based on average-hit method - GTao ZHEN; Qi ZENG (Dianxin kexue)
The pseudo-random M-ary sequence (such as RS code,polynomial code and low-hit zone FH code and so forth) is widely adopted as FH code in FH-CDMA system.However,the performance of FH-CDMA system employing FH sequence is usually evaluated by simulation,and lack of substantial theoretical analysis.A systematic method for modeling the frequency-hit according to the pre-assigned FH code was proposed; then with the proposed model,the analysis for multi-access interference(MAI)was simplified.The numerical relation between the properties of pseudo-random FH code and the error-rate performance of FH-CDMA system was established.Theoretical and simulation results show that the proposed average-hit model is an efficient method to evaluate the frequency hit and the error-rate of pseudo-randomly FH-CDMA system.Meanwhile,the optimal error-rate low-bound of FH-CDMA system which can achieved by pseudo-random FH code is shown in the conclusion.